2018
DOI: 10.1002/ca.23081
|View full text |Cite
|
Sign up to set email alerts
|

Variability in facial‐muscle innervation: A comparative study based on electrostimulation and anatomical dissection

Abstract: Facial-nerve palsy is the most common complication during facial surgery. However, there are few detailed reports on the distribution of the terminal branches of the facial nerve to the mimetic muscles. This also applies to the communicating branches. The aim of our study was to assess the variability of communicant and terminal branches of the facial nerve in humans. This prospective study involved anatomical dissections and intraoperative electric stimulation of facial nerves. We first performed 30 dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Nevertheless, the peripheral branching and intercommunication of the facial branches were highly variable [24]. In our experience on 10 hemi heads we observed a different pattern of facial nerve branching between subjects and between right and left sides from the same subject.…”
Section: Facial Nerve-cnviimentioning
confidence: 58%
“…Nevertheless, the peripheral branching and intercommunication of the facial branches were highly variable [24]. In our experience on 10 hemi heads we observed a different pattern of facial nerve branching between subjects and between right and left sides from the same subject.…”
Section: Facial Nerve-cnviimentioning
confidence: 58%
“…Meta-analysis reports [10] conclude that the MMN more often manifests with single or double branches with a prevalence of 35% and shows most frequent anastomosis with the buccal branch of the facial nerve (20%) and more rarely anastomosis with mental nerve (12%), cervical branch of the facial nerve (5%), great auricular nerve (2%), transverse cervical nerve (2%), cervical (5%), and zygomatic branch (1%) of the facial nerve. De Bonnecaze et al [40] performed anatomical dissection studies to report the variation in the innervation of facial muscles and distribution of communications with the facial nerve. They concluded that the MMN showed fewer communicating branches in comparison to other facial nerve branches and commented that the lower lip muscles displayed the least supplemental innervation by MMN.…”
Section: Relation To Number Of Branches/anastomosismentioning
confidence: 99%
“…La inervación motora de la cara viene principalmente del séptimo nervio craneal o par craneal VII, llamado por ello "nervio facial". Este par craneal VII emerge en la cara justo por debajo de la oreja y se subdivide en cinco ramas: temporal y zigomática, que inervan preferentemente la parte superior de la cara, y las ramas bucal, mandibular y cervical, que inervan preferentemente la parte inferior de la cara y el cuello, aunque se ha comprobado que hay variabilidad de un individuo a otro (De Bonnecaze et al, 2019;Raslan et al, 2017).…”
Section: La Importancia De La Gestualidad En La Expresión De La Hipótesisunclassified